Conocimientos expertos y la delimitación de las causas deuna problemática socioambiental: El caso de la producción debioetanol en Córdoba, Argentina - Arriaga, Julian (2024)
Disputes over the characterization of environmental problems involve the participation of various social stakeholders, who are unequally qualified to participate in the public arena. Among these, expert knowledge is mostly authorized to be part of the resolution of the problems. is paper seeks to analyze the conceptual and epistemic aspects involved in the determination of the causes of the problems related to the bioethanol production of the Porta Hermanos Company. It is observed that the approaches of the chemical experts lead to the absence of establishing causal links between the factory and the reported pollution.